Minimally Invasive Surgery of the Pancreas (Updates in Surgery,, 2018)
This book provides a unique and comprehensive overview of minimally invasive (MI) surgical options for the treatment of pancreatic diseases. The opening chapters present the state of the art of minimally invasive (MI) pancreatic resection according to the 2016 IHPBA Conference, offer information on the safe dissemination of MI pancreatic surgical techniques, and discuss preoperative evaluations protocols and surgical planning options. The book subsequently investigates the full range of currently available minimally invasive techniques, which includes: biliary and gastric bypass, ampullectomy, central and distal pancreatectomy, laparoscopic and robotic pancreatoduodenectomy, and robotic pancreas transplantation. Combining the acknowledged expertise of the Italian school in pancreatic surgery and the contributions of many leading international experts, the book offers a valuable guide for all surgeons who perform this complex surgery, as well as for residents and fellows-in-training.